Prospect Theory predictions in the field: Risk seekers in settings of weak accounting controls. Issue 1 (1st November 2014) - Abdel-khalik, A. Rashad
Abstract : In his review of 30 years of research in Prospect Theory, Barberis (2013) notes that support for Prospect Theory had come mainly from the laboratory. In this paper, I write about a recurring phenomenon in real life that is consistent with Prospect Theory predictions in decision-making loss domain. The 60 cases noted in this paper are associated with specific risk seekers that had cost more than $140 billion (an average of $2.33 billion per case). Given space consider– ations, I provide synopses for 14 cases. A few of these cases have been discussed in the extant literature in connection with internal control, but were not considered from the perspective of Prospect Theory. It is striking that these cases are costly, all participants are young men, and almost all had followed the gambler's martingale strategy – i.e., double down. While these cases are informative about risk-seeking behavior, they are not sufficiently systematic to be subjected to stylized archival research methods.